Characterization of neonates affected by neonatal abstinence syndrome: An integrative review (Research, Society and Development, 2022)
The Neonatal Abstinence Syndrome (NAS) is defined as the situation of newborns who were exposed to different types of substances used by their mothers while pregnant, that is, still in their intrauterine phase, making them physically dependent on them, which can cause malformations and harmful effects to the nervous, gastrointestinal and respiratory systems. Objective: To characterize neonates affected by withdrawal syndrome and to list the types of psychoactive drugs that most affect them and their clinical manifestations. Methodology: Integrative review study with search in electronic databases SCIELO, PUBMED and VHL, from 2011 to 2021, without language restrictions. Results and Discussion: It was possible to identify the characteristics of newborns with substance abuse withdrawal syndrome, as well as to list the clinical manifestations that these newborns present, according to the type of substance used by the mother during pregnancy. It was also noted the importance of the multidisciplinary team when dealing with this pathology and the difficulty in making a diagnosis, since this is a subject that has not been so widely studied. Final considerations: In view of the actions analyzed, it was noted the importance of implementing strategies aimed at exploring the characteristics that these newborns present when exposed to narcotic substances during intrauterine life, thus facilitating the evaluation and early detection of this syndrome.